A validated LC–MS/MS method for neurotransmitter metabolite analysis in human cerebrospinal fluid using benzoyl chloride derivatization. (October 2015) - Cox, Jennifer M; Butler, Jon P; Lutzke, Barry S; Jones, Barry A; Buckholz, John E; Biondolillo, Raymond; Talbot, Jayne A; Chernet, Eyassu; Svensson, Kjell A; Ackermann, Bradley L
Background: Human cerebrospinal fluid (CSF) is often acquired in Phase I clinical trials to assess the CNS penetration of new pharmacological agents and to search for biomarkers associated with PD effects. Robust methods for neurotransmitter metabolites in CSF have proven elusive, in part due to inadequate reversed phase LC retention.Results: Benzoyl chloride derivatization was used to promote retention for LC–MS/MS for a panel of neurotransmitter metabolites while delivering a concise method for sample preparation.Conclusion: A validated assay in human CSF was obtained for 3, 4-dihydroxyphenylacetic acid, homovanillic acid, 3, 4-dihydroxyphenylglycol and 5-hydroxyindoleacetic acid. This method is differentiated from other LC–MS/MS methods by delivering results in line with full regulatory expectations.